Lesion-symptom mapping corroborates lateralization of verbal and nonverbal memory processes and identifies distributed brain networks responsible for memory dysfunction. (August 2022) - Mock, Nadia; Balzer, Christian; Gutbrod, Klemens; De Haan, Bianca; Jäncke, Lutz; Ettlin, Thierry; Trost, Wiebke
Abstract: Memory disorders are a common consequence of cerebrovascular accident (CVA). However, uncertainties remain about the exact anatomical correlates of memory impairment and the material-specific lateralization of memory function in the brain. We used lesion-symptom mapping (LSM) in patients with first-time CVA to identify which brain structures are pivotal for verbal and nonverbal memory and to re-examine whether verbal and nonverbal memory functions are lateralized processes in the brain. The cognitive performance of a relatively large cohort of 114 patients in five classic episodic memory tests was analysed with factor analysis. Two factors were extracted that distinguished the verbal and nonverbal components of these memory tests, and their scores were subsequently tested for anatomical correlates by combining univariate and multivariate LSM. LSM analysis revealed for the verbal factor exclusively left-hemispheric insular, subcortical and adjacent white matter regions and for the nonverbal factor exclusively right-hemispheric temporal, occipital, insular, subcortical and adjacent white matter structures. These results corroborate the long-standing hypothesis of a material-specific lateralization of memory function in the brain and confirm a robust association between right temporal lobe lesions and nonverbal memory dysfunction. The right-hemispheric correlates for the nonverbal aspects of episodic memory include not only classic memory structures in the medial temporal lobe but also a more distributed network that includes cortical and subcortical structures also known for implicit memory processes.